Nanocrystalline (NixCo(1-x))3(PO4)2@FeSe2/NF as a promising OER electrocatalyst for alkaline water electrolysis - Christi, Darren Sebastian; Selvaraj, Kaliaperumal (International Journal of Hydrogen Energy, 2024)
Affordable and sustainable hydrogen production is the need of the hour owing to the mounting global pursuit for the hydrogen economy. Water splitting is the premier go -to method to produce green hydrogen at a larger scale in which the half -cell Oxygen Evolution Reaction (OER) demands a larger amount of energy expenditure due to its sluggish kinetics. Hence, designing an efficient OER electrocatalyst, especially for alkaline water electrolysis that offers alternatives to the usage of precious group metals is a pressing priority. Herein, we report a novel nanocrystalline electrocatalyst consisting of two components, namely cobalt nickel phosphate and iron diselenide synthesised via a two-step electrodeposition at room temperature. The combination of the two components on the porous nickel foam substrate exhibits an overpotential of 272 mV at 100 mA/cm2 in 1 M KOH showing a low Tafel slope of a mere 38 mV/dec with appreciable retention even after 24 h of stability test at a relatively higher current density. The surface reconstruction that occurs when FeSe2 is electrodeposited on (Ni0.35Co0.65)3(PO4)2@NF and the synergy between the two components is the primary reason for the improved performance. Thus, this work highlights the ambient synthesis of a highly durable earth -abundant metal -based electrocatalyst which exceeds the performance of the standard Ru/C by a decent margin.
Keywords: Alkaline Water Electrolysis; Ambient synthesis; Electrodeposition; Non-PGM based Electrocatalyst; OER